Using Photovoice to Understand Perspectives on Safe Infant Sleep Practices among Caregivers Enrolled in Perinatal Home Visiting. Issue 47 (22nd September 2020) - Kihlström, Laura; Agu, Ngozichukwuka; Dorjulus, Barbara; Prieto, Concha; Chandran, Vidya; Alastre, Stefania; Rojas, Dogeli; Birriel, Pamela C.; Marshall, Jennifer
Abstract: Sudden and unexpected infant death (SUID), often associated with unsafe infant sleep practices, remains a leading cause of infant mortality in the United States. Maternal, Infant, and Early Childhood Home Visiting (MIECHV) programs provide evidence-based individualized education, support, and resources to promote infant and child health, including promotion of safe infant sleep guidelines. The purpose of this qualitative evaluation was to explore barriers, facilitators, and home visitor influences on infant sleep practices; this component elicited caregivers' perspectives using Photovoice methodology. Photovoice is a community-based participatory research method which aims to bring forward participants' perspectives and everyday experiences through visual means. Five MIECHV participants submitted 21 pictures that were discussed in individual interviews. The main facilitators were access to appropriate furnishing, knowledge about safe sleep practices, and effective bedtime routines. Barriers included housing-related issues, other caregivers' practices, and caring for siblings. These results highlighted the importance of the practitioner-client relationship and inform the program on factors that affect parents' decision-making and infant sleep practices.